Penilaian Kondisi Jalan dengan Metode Surface Distress Indeks (SDI) pada Ruas Jalan Kabupaten di Kecamatan Penukal Utara - Irawan, Agus; Saloma, Saloma; Putra Usman, Arie (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The increasing mobility of the population in Penukal Abab Lematang Ilir Regency in line with the growth and development of residential areas in the district has resulted in an increasing need for the provision of adequate transportation facilities and infrastructure. To meet the need for transportation facilities and infrastructure, a road infrastructure development policy was implemented. One of the policies for developing road infrastructure is data regarding road conditions in Penukal Abab Lematang Ilir Regency. Updating data on district road conditions in North Penukal District using the Surface Distress Index (SDI) Method and by ranking the steady condition of roads in North Penukal District, Penukal Abab Lematang Ilir Regency. The results of the survey of district roads in North Penukal District in 2024 were in good condition along 151,873 Km or 52.038%, moderate condition along 25,216 Km or 8.640%, slightly damaged condition, 9,397 Km or 3.220% and heavily damaged 105,364 Km or 36,102% with road stability of 60.678% and unstable conditions of 39.322%.